A compact neutron spectrometer for detecting neutrons produced by cosmic rays - Jarvie, Erin (Department of Physics, 2024)
The high energy secondary neutron fields from cosmic radiation that are found in aviation and space environments have impacts on both biological and technological systems. A compact neutron spectrometer that is safe to operate in an aviation environment and suitable for detecting these secondary neutrons has been developed. The detector consisting of a (0.6×0.6×12.0 cm3 ) EJ-276 plastic scintillator coupled to a silicon photomultiplier (SiPM) has been designed, constructed and characterised with neutrons up to 62.5 MeV at the UCT n-lab, IRSN AMANDE and iThemba LABS fast neutron facilities. The compact detector displays good quality pulse shape discrimination for the separation of neutron and gamma ray events. Neutron energy spectra were obtained through time-of-flight (ToF) measurements and spectrum unfolding. The energy spectra obtained from ToF display energy resolution similar to that obtained by a BC-501A reference detector. A matrix of measured response functions for neutrons with energies between 11 MeV and 62 MeV at 3 MeV intervals selected by ToF has been constructed for the detector. The response functions have been used to successfully unfold neutron energy spectra across the entire range of energies.